Listening Comprehension Achievement: Comparing Learning Method and Game in EFL Learning - Rizal Arisman; Yuli Yastiani; Wa Ode Hanafiah; Irnawati; Poppy Satriani (Universitas Sarjanawiyata Tamansiswa, 2025)
The Chinese Whisper game and the Question Students Have method can be used in teaching listening comprehension. This research aims to determine whether there is a significant difference in listening comprehension between students taught using the Chinese Whisper game and those taught using the Question Students Have method and decide which is better to improve listening comprehension. This research used a quantitative approach of quasi-experimental design by involving 45 students selected using the purposive cluster sampling technique in grade eight of junior high school in Baubau, Southeast Sulawesi. Data were obtained using a test. They were analyzed by applying three steps: descriptive analysis, normality test, and inferential analysis using the Wilcoxon test, Paired Sample test, and Mann-Whitney U test. The result indicated that students' listening comprehension improved after being taught using the Chinese Whisper and the Question Students Have method. The conclusion is that there is a significant difference in listening comprehension after those were applied. The Chinese Whisper game improves listening comprehension higher than the Question Students Have method.